Study of Jet Modification in Relativistic Heavy-Ion Collisions - Campos, Leonardo Barreto de Oliveira (2021)
The study of jets, algorithmic representations of collimated sprays of particles, in relativistic heavy-ion collisions can illuminate the underlying physics of heavy ion experiments, as the ones in the Large Hadron Collider (LHC) and Relativistic Heavy-Ion Collider (RHIC). These experiments enable the production of the Quark-Gluon Plasma, a new state of matter characterized by its extreme energy density and temperature, which modifies the hard-scattered partons traveling through it and, consequently, the jets they produce. Analyses regarding jets as the main subject may recover information about the medium and implications to the Quantum Chromodynamics (QCD) theory. This work applies the Monte Carlo event generators JEWEL (Jet Evolution With Energy Loss) and PYTHIA for the simulation of observables comparable to current experimental research. The impact of a realistic description of the medium, provided by the state-of-the-art (2+1)D v-USPhydro code, in the azimuthal distribution and energy modification of jets is the main focus of this study. All observables are presented for central and peripheral lead-lead collisions at 5.02 TeV, following the experimental setup of the LHC Run-2, for anti-$k_T$ jets with multiple jet radii $R$. The jet nuclear modification factor $R_{AA}$ simulated presents good agreement with experimental data for central collisions only. The evolution of the results in terms of centrality and $R$ indicates a possibility of better understanding of medium response in the JEWEL framework. The realistic hydrodynamics models behave differently to JEWEL\'s longitudinal-only expansion, mainly in the circumstances where less quenching is expected. The correlation between the jet azimuthal distribution and those generated by soft particles resulted from the realistic medium profiles enables the event-by-event calculation of higher-order jet anisotropic flow coefficients that can be compared to experimental measurements. The simulations show a transverse momentum-dependent elliptic flow $v_2$ and, for the first time, a positive triangular flow $v_3$.